Naughty in Nice [large type] - Bowen, Rhys (Bowen, Rhys. Royal Spyness mysteries., 2012)
Lady Georgiana Rannoch has once again been called into service by Her Majesty the Queen. This time she's sent to Nice on a secret assignment that's nothing to sneeze at: recover the Queen's stolen snuff box. While in Nice, Coco Chanel herself asks Georgie to model her latest fashion - and a necklace belonging to the Queen is stolen on the catwalk. Now, Georgie has to find two priceless items - and solve a murder.